Development of QR Code-Based Big Book Media to Improve the Literacy Skills of Elementary School Students in Phase A - Sudarmiani; Belina Listyo Ningtyas (Jurnal Pedagogi dan Pembelajaran, 2026)
The low literacy skills of Phase A students are a real challenge in elementary schools, supported by the limited interactive and contextual learning media. This study aims to (1) analyze the need for media development, (2) develop a prototype of QR Code-based BigBook media, and (3) test its effectiveness in improving literacy skills. The subjects of the study were 47 students and 3 teachers from three public elementary schools in Madiun City. Data were collected through expert validation sheets, literacy tests (pre-test and post-test), observations, and questionnaires. The instruments were analyzed descriptively quantitatively, followed by paired sample t-tests and N-Gain calculations. The results of expert validation of material, media, and language obtained an average percentage of 94.28% (Very Feasible category). The results of statistical tests showed a significant increase in literacy skills with a t-value of 22.94 (p < 0.05) and N-Gain of 0.76 (High category). The conclusion of the study states that the developed QR Code-based BigBook media is feasible and effective. The implication is that this media can be used as an innovative model to support enjoyable and differentiated literacy learning in elementary schools.